Mud-packing frog: A novel breeding behaviour and parental care in a stream dwelling new species of Nyctibatrachus (Amphibia, Anura, Nyctibatrachidae) - Gururaja, Kotambylu Vasudeva; Dinesh, K. P.; Priti, H.; Ravikanth, G. (Zootaxa, 2014)
Reproductive modes are diverse and unique in anurans. Selective pressures of evolution, ecology and environment are attributed to such diverse reproductive modes. Globally forty different reproductive modes in anurans have been described to date. The genus Nyctibatrachus has been recently revised and belongs to an ancient lineage of frog families in the Western Ghats of India. Species of this genus are known to exhibit mountain associated clade endemism and novel breeding behaviours. The purpose of this study is to present unique reproductive behaviour, oviposition and parental care in a new species Nyctibatrachus kumbara sp. nov. which is described in the paper. Nyctibatrachus kumbara sp. nov. is a medium sized stream dwelling frog. It is distinct from the congeners based on a suite of morphological characters and substantially divergent in DNA sequences of the mitochondrial 16S rRNA gene. Males exhibit parental care by mud packing the egg clutch. Such parental care has so far not been described from any other frog species worldwide. Besides this, we emphasize that three co-occurring congeneric species of Nyctibatrachus, namely N. jog, N. kempholeyensis and Nyctibatrachus kumbara sp. nov. from the study site differ in breeding behaviour, which could represent a case of reproductive character displacement. These three species are distinct in their size, call pattern, reproductive behaviour, maximum number of eggs in a clutch, oviposition and parental care, which was evident from the statistical analysis. The study throws light on the reproductive behaviour of Nyctibatrachus kumbara sp. nov. and associated species to understand the evolution and adaptation of reproductive modes of anurans in general, and Nyctibatrachus in particular from the Western Ghats.